Traumatic Ulceration of the Vestibular Mucous Membrane After Insertion of Four Mini-Implants in the Atrophied Mandible: A Case Report - Domagoj Kilić; Sanja Peršić-Kiršić; Asja Čelebić (Hindawi Limited, 2024)
This clinical report describes how a decubital ulcer arose from the direct contact of the vestibular movable mucous membrane against mini-implant balled-type heads after the mini-implant insertion in the edentulous atrophic mandible of a 78-year-old patient who was not wearing a conventional mandibular complete denture for more than 10 years. Due to severe alveolar ridge atrophy, mini-implant insertion (2.0 mm wide) was an option without extensive surgical procedures. The patient signed the informed consent. A few days after the implant insertion, injury, inflammation, and induration of the vestibular movable mucous membrane were observed on the movable vestibular mucosa on the right side, opposing the mini-implants. The cause of inflammation was attributed to increased perioral muscle tonus which pushed the movable mucosa onto the mini-implant heads and caused mechanical trauma. During the period of edentulism, the perioral muscle tonus increased, directing the mucous membrane of the lips and cheeks against residual ridge to enable food comminution. To treat the persistent decubitus, a bulk of dental composite resin was placed around mini-implant heads and light-cured to protect the mucosa from further mechanical trauma, as the patient did not possess an old mandibular denture to cover the mini-implant heads. Vestibuloplastic surgery (disinsertion of movable attachments and deepening of the vestibulum) was also done. After the surgery, a silicone splint, resembling an occlusal rim, was made to protect the mucous membrane, keep medicaments for faster epitalization in place, to decrease perioral muscle tonus before the new dentures' delivery, and to prevent movable tissue relapse. The custom impression, jaw relationship determination, and try-in of the artificial teeth setup were made with sutures still in place. After the denture delivery and implant loading, the patient was instructed to sleep with the dentures to protect the movable mucous membrane. One year later, almost no peri-implant marginal bone loss was observed, attached and peri-implant mucosa were healthy, and the patient was delighted.